Contribution to the Recycling of Rotary Kiln Dust in Nickeliferous Laterite Reduction. Reductive Behavior of the Dust - Elias Rigopoulos (The Minerals, Metals and Materials Society, 2004)
In the present study the reductive behavior of dust from the rotary kilns (RK), in ferronickel production from nickeliferous Greek laterites, is investigated. The study concerns dust of various origins (washing towers, electrostatic filters, polycyclones) and pellets made from the dust. Reducibility was studied in the temperature range of 700 °C to 850 °C in a laboratory tube furnace. Experimental results showed that reduction degree increases with temperature up to about 800 °C. The rate of reduction is great during the first minutes, giving a reduction degree R% equal to about 25%, in only a few minutes. After this, the rate is decreasing until it diminishes to zero after about 10-20 minutes of reaction. Maximum reduction degree achieved is 26 to 28%. Rates and reduction degrees at various temperatures are higher for the dust samples than those of the respective pellet samples. Keywords: Ferronickel, metallurgy, laterites, pellets, reduction